Syntrophic Growth of Geobacter sulfurreducens Accelerates Anaerobic Denitrification - Wan, Yuxuan; Zhou, Lean; Wang, Shu; Liao, Chengmei; Li, Nan; Liu, Weitao; Wang, Xin (Frontiers in Microbiology, 2018)
Nitrate is considered as a contamination since its over discharging to water incurs environmental problems. However, nitrate is an ideal electron sink for anaerobic pollutant degraders desiring electron acceptors due to the high redox potential. Unfortunately, not all degraders can directly reduce nitrate, and the anaerobic direct interspecies electron transfer between degraders and denitrifiers has not been confirmed yet. Here we demonstrated that syntrophic growth of G. sulfurreducens PCA with denitrifying microbial community at anaerobic condition eliminated the lag phase of 15 h and improved the denitrification rate by 13 ~ 51 % over a broad C/N ratio of 0.5 to 9. Quantitative PCR revealed that G. sulfurreducens selectively enhanced the expression of nirS coding for a cytochrome cd1-nitrite reductase, resulting in a fast and more complete denitrification. Geobacter also selectively enriched its potential denitrifying partners - Diaphorobacter, Delftia and Shinella - to form spherical aggregates. More studies of the binary culture system need to be carried out to confirm the syntrophic mechanism of Geobacter and denitrifiers in the future. These findings extend our knowledge on understanding the anaerobic bacterial interspecies electron transfer in the denitrification process, which has broader implications in fast selection and stabilization of denitrifiers in wastewater treatment plant, and general understanding of ecology for nitrogen and metal cycling.